Genomic analysis of Sweet potato feathery mottle virus from East Africa - Wokorach, G.; Otim, G.; Njuguna, Joyce N.; Edema, H.; Njung'e, V.; Machuka, Eunice M.; Yao, Nasser; Stomeo, Francesca; Echodua, R. (Elsevier, 2020)
Sweet potato feathery mottle virus is a potyvirus that infect sweet potato. The genome of the virus was analysed to understand genetic diversity, evolution and gene flow. Motifs, nucleotide identity and a phylogenetic tree were used to determine phylogroup of the isolates. Gene flow and genetic diversity were tested using DnaSP v.5. Codons evolution were tested using three methods embedded in Datamonkey. The results indicate occurrence of an isolate of phylogroup B within East Africa. Low genetic differentiation was observed between isolates from Kenya and Uganda indicating evidence of gene flow between the two countries. Four genes were found to have positively selected codons bordering or occurring within functional motifs. A motif within P1 gene evolved differently between phylogroup A and B. The evidence of gene flow indicates frequent exchange of the virus between the two countries and P1 gene motif provide a possible marker that can be used for mapping the distribution of the phylogroups.